IMPLEMENTASI MANAJEMEN PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PROGRAM SKUA DI MA UMMUL QURO PUTRI PAMEKASAN - Fitria Ningsih; Akh Syaiful Rijal (STAI Ma'had Aly Al-Hikam Malang, 2021)
This study aims to analyze the implementation of SKUA program management in shaping the religious character of students at MA Ummul Quro Putri Pamekasan. The method used is a qualitative approach with descriptive analysis type. Data collection techniques were obtained through observation, interviews and documentation. Then the data collected was analyzed with the stages of data condensation activities, data presentation, and drawing conclusions or verification. The results of the research that have been conducted show that: First, the process of implementing the SKUA program management in shaping the religious character of students at MA Ummul Quro Putri consists of five stages, planning, organizing, implementing, monitoring and evaluating. Second, the impact obtained is to deepen students scientific treasures, slowly students begin to learn daily practices with discipline, each student begins ti be directed ti have a religious character and students begin to get used ti religius attitudes and traits. Third, the inhibiting factor is the lack of awareness of students how important the SKUA program is in daily life, student personal differences and different environmental factors have a negative impact on the formation of students religious character. Solution that can be done to overcome these inhibiting factors are by firt identifying the problems faced by students and then looking for solutions, providing sanctions related to religion, and providing special guidance to overcome problems that cannot be solved by sanctions.